2018
DOI: 10.4174/astr.2018.94.5.223
|View full text |Cite
|
Sign up to set email alerts
|

Pegfilgrastim for primary prophylaxis of febrile neutropenia in breast cancer patients undergoing TAC chemotherapy

Abstract: PurposePrimary prophylaxis with granulocyte colony-stimulating factor can effectively prevent febrile neutropenia (FN) during breast cancer treatment. The aims of this study were to evaluate the incidence of FN and the ANC profile in patients undergoing chemotherapy and pegfilgrastim primary prophylaxis.MethodsPatients receiving 6 cycles of adjuvant docetaxel, doxorubicin, and cyclophosphamide (TAC) chemotherapy were included in this study. Pegfilgrastim was administered with analgesics 24 hours after treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 26 publications
0
18
0
2
Order By: Relevance
“…Moreover, plinabulin did not affect endogenous G-CSF levels in bone marrow or plasma in the models tested. Data therefore indicate that plinabulin may serve as an alternative therapy to G-CSF for prophylactic CIN therapy and should also be considered for testing in combination with G-CSF therapies, especially in settings where adequate ANC control by G-CSF therapy is lacking [e.g., 8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, plinabulin did not affect endogenous G-CSF levels in bone marrow or plasma in the models tested. Data therefore indicate that plinabulin may serve as an alternative therapy to G-CSF for prophylactic CIN therapy and should also be considered for testing in combination with G-CSF therapies, especially in settings where adequate ANC control by G-CSF therapy is lacking [e.g., 8].…”
Section: Discussionmentioning
confidence: 99%
“…G-CSF adverse effects include bone pain, splenic rupture, acute respiratory distress syndrome, allergic reactions including anaphylaxis and allergies to acrylics, sickle cell disorder, glomerulonephritis, capillary leak syndrome, leukocytosis and the potential for tumor growth stimulatory effects on malignant cells [5,7]. Finally, with more aggressive chemotherapy regimens such as Taxotere ® + Adriamycin ® + cyclophosphamide (TAC), grade 3 or 4 neutropenia still occurs in > 90% of patients, despite G-CSF prophylactic therapy [8]. To address these issues, novel non-GSF-based treatments for CIN are being sought as alternatives or supplements to G-CSF therapies [7].…”
Section: Introductionmentioning
confidence: 99%
“…The use of long-acting G-CSF is the most important way to overcome the limitations caused by the hematologic toxicity of the TAC regimen. Treatment with long-acting G-CSF reduces FN and results in better supportive care and an improved quality of life in breast cancer patients [ 13 16 17 21 ]. In our study, the incidence of FN decreased from 54.2% to 21.2% in patients, and from 36.1% to 9.1% in all chemotherapy cycles, after the use of primary prophylactic pegfilgrastim.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in Korea reported that the overall frequency of FN during adjuvant TAC chemotherapy was significantly higher than that observed in previous studies conducted in Western countries (42.5%–63.4% vs. 17%–26%) [ 18 19 20 ]. However, only 1 study with a small sample size reported the clinical effect of primary prophylactic therapy using pegfilgrastim on the incidence of FN during adjuvant TAC chemotherapy in Korea [ 21 ]. Therefore, the aim of the current study was to evaluate not only the difference in the incidence of FN but also the difference in the risk of FN-related complications and hospitalization according to whether Korean patients with advanced breast cancer received primary prophylactic support with pegfilgrastim during adjuvant TAC chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Adapun faktor risiko yang berpengaruh secara langsung terhadap insiden neutropenia diantaranya adalah usia (p = 0,000), LPT (p = 0,037), jenis kemoterapi (p = 0,000), siklus kemoterapi (p = 0,000), dan regimen kemoterapi (p = 0,000 [7,15]. Penggunaan profilaksis G-CSF pada pasien dengan usia >65 tahun yang menderita solid tumor dapat menurunkan perawatan di rumah sakit akibat FN dari 9% menjadi 5% [16].…”
Section: Analisis Faktor Risikounclassified